2003
DOI: 10.1021/jf0302254
|View full text |Cite
|
Sign up to set email alerts
|

Study of Aged Cognac Using Solid-Phase Microextraction and Partial Least-Squares Regression

Abstract: Headspace solid-phase microextraction (SPME) and GC-MS were used to analyze 17 commercial French Cognac brandies (9 young and 8 well-aged, ranging in age from 3 to 55 years). Sixty-four volatiles were chosen on the basis of chromatographic separation and/or known odor importance. Chromatographic peaks were manually integrated and the peak area data analyzed using partial least-squares (PLS) regression to study relationships between volatile composition (X variables) and age (Y variable). When only those compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 18 publications
1
32
0
Order By: Relevance
“…They developed a reliable prediction model having a correlation coefficient (R 2 ) of 0.998, slope of 0.996, root mean square error (RMSE) value of 1.17, and an offset value of 0.081 using 33 variables (including 24 esters, four methyl ketones, two aldehydes, two alcohols, and one lactone). Watts et al (2003) also showed that their model could predict the age of cognac with a reduced subset from the 33 original variables. Using two subsets containing four methyl ketones and 13 ethyl esters either individually or together, they could develop PLS prediction models with R 2 values >0.934 and RMSE error values <6.47.…”
Section: B Alcoholic and Non-alcoholic Beveragesmentioning
confidence: 97%
See 1 more Smart Citation
“…They developed a reliable prediction model having a correlation coefficient (R 2 ) of 0.998, slope of 0.996, root mean square error (RMSE) value of 1.17, and an offset value of 0.081 using 33 variables (including 24 esters, four methyl ketones, two aldehydes, two alcohols, and one lactone). Watts et al (2003) also showed that their model could predict the age of cognac with a reduced subset from the 33 original variables. Using two subsets containing four methyl ketones and 13 ethyl esters either individually or together, they could develop PLS prediction models with R 2 values >0.934 and RMSE error values <6.47.…”
Section: B Alcoholic and Non-alcoholic Beveragesmentioning
confidence: 97%
“…Most of the volatiles extraction for the alcoholic beverages were carried out at 22°C to 55°C, and the preferred desorption temperatures were between 200°C to 250°C (Table 2). Watts et al (2003) used SPME to extract volatiles from cognac and used the extracted volatiles to develop a partial least squares (PLS) regression model to predict the aging of cognac. They developed a reliable prediction model having a correlation coefficient (R 2 ) of 0.998, slope of 0.996, root mean square error (RMSE) value of 1.17, and an offset value of 0.081 using 33 variables (including 24 esters, four methyl ketones, two aldehydes, two alcohols, and one lactone).…”
Section: B Alcoholic and Non-alcoholic Beveragesmentioning
confidence: 99%
“…Merchandising as a science is continually evolving, resulting in development of new science based commodity research indicators which may be used for assessing quality and authenticity of the components used for food products (Wakefield 2002;Watts 2003;Dzhakhangirova, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Various researches have been conducted for the assessment of proteins and amino acids characteristics in vegetable and natural products (Wakefield, 2002;Watts, 2003;Woolfe, 2004). Further, researcher have developed a new objective as commodity research indicator of vegetable proteins" quality i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation